NUPTIAL AGREEMENT IN MUSLIM MARRIAGE: A JURISTIC ANALYSIS - Abdullahi Busari, Saheed (Jurnal Fiqh, 2024)
The nuptial agreement is been gaining attraction in the Muslim environment in recent times because of the assumed benefit to protect either of the marital partners in the advent of divorce or separation. Prenuptial clauses usually take effect immediately after marriage consummation and every party can lay claim to the agreement in the event of a breach of agreement while postnuptial agreements are clauses agreed upon during the marriage period. Although there are complaints that Muslims from Western and non-Islamic societies might need prenuptial agreement in the place of khulʼ (redemption) to protect either party in the case of future divorces or separation, however, there are concerns about the rate of interest in the new couples from Muslim society opting for a prenuptial agreement. This study explores the concepts of prenuptial and postnuptial and their associated use by Muslim couples in contemporary reality. The study will examine why Muslim couples from Islamic society are opting for nuptial agreement rather than khulʼ regulations in Islamic law and the need to identify essential thresholds in juristic conditioning for nuptial agreements in a Muslim marriage, especially in the case of Shartu fāsid (invalid conditions) in a marriage agreement. The study uses a doctrinal approach to gathering and analysis of data from an Islamic perspective. The study proposed useful suggestions from the finding on juristic conditioning in the application of prenuptial and postnuptial agreements in Muslim society.